Synthesis of novel semi-squaraine derivatives and application in efficient dye-sensitized solar cells. (June 2019) - Kabanakis, Antonios N.; Bidikoudi, Maria; Elsenety, Mohamed M.; Vougioukalakis, Georgios C.; Falaras, Polycarpos
Abstract: A series of novel semi-squaraine sensitizers with various architectures and anchors have been synthesized and utilized in dye-sensitized solar cells. These dyes combine indole- or carboline-based electron rich units with strongly electron-withdrawing cyanoacetate moieties or other functional anchoring moieties. They were thoroughly characterized as per their structural, optical and electrochemical properties and the behavior of the as-prepared solar cells were examined in detail using linear sweep voltammetry, electrochemical impedance spectroscopy and DFT calculations. Amongst the herein reported dyes, AKSq1, incorporating a free hydroxyl group directly attached to the squarate ring, exerts the optimum performance in dye-sensitized solar cells, despite the fact that this dye presents the lowest extinction coefficient among the molecules under study. AKSq1 demonstrates power conversion efficiency of 2.63%, about 14% higher than the efficiency obtained with the corresponding reference dye, the commercially available, high-performance, metal-free dye D35, under the same cell fabrication and measuring conditions. This result is attributed to the presence of free squaryl hydroxyl moiety ensuring efficient dye chemisorption and the existence of a lipophilic dodecyl group preventing the aggregation of the squaraine sensitizer onto the semiconductor's surface either by itself, or via increased intercalation of the C12 chain with the chenodeoxycholic acid coadsorbent. Graphical abstract: Image 1 Highlights: Novel semi-squaraines with various architectures synthesized and characterized. Semi-squaraine dyes bearing a long hydrophobic dodecyl groups. Effective incorporation of semi-squaraines in dye-sensitized solar cells (DSCs). DSCs using organic dyes presenting high power conversion efficiencies.